Quinoid‐Resonant Conducting Polymers Achieve High Electrical Conductivity over 4000 S cm−1 for Thermoelectrics. Issue 10 (23rd August 2018) - Yuan, Dafei; Liu, Liyao; Jiao, Xuechen; Zou, Ye; McNeill, Christopher R.; Xu, Wei; Zhu, Xiaozhang; Zhu, Daoben
Abstract: New conducting polymers polythieno[3, 4‐ b ]thiophene‐Tosylate (PT b T‐Tos) are prepared by solution casting polymerization. Through tuning the alkyl group of T b T, the electrical conductivity can be effectively enhanced from 0.0001 to 450 S cm −1 . Interestingly, the electrical conductivity of PT b T‐C1‐Tos increases significantly from 450 S cm −1 at room temperature to 4444 S cm −1 at 370 K, which is disparate from polyethylenedioxythiophene‐Tos exhibiting metallic conducting behavior. Quasi‐reversible phase transformation with temperature from 3D crystallites to lamellar‐stacking coincides with the increasing electrical conductivity of PT b T‐C1‐Tos with heating. Methyl‐substituted PT b T‐Tos with the best electrical property is further utilized for thermoelectrics and a power factor as high as 263 µW m −1 K −1 is obtained. It is believed that PT b T‐Tos will be a promising family of conducting polymers for solution‐processed organic electronics. Abstract : Conducting quinoid‐resonant polymers polythieno[3, 4‐ b ]thiophene (PT b T)‐tosylate are prepared by solution‐casting polymerization. Through fine tuning of the alkyl group, the electrical conductivity can be effectively enhanced from 0.0001 to 450 S cm −1 . The great potential of PT b T‐C1‐Tos is demonstrated in thermoelectrics, which surmounts the state‐of‐the‐art conducting polymer, polyethylenedioxythiophene (PEDOT)‐Tos.